Black‐box noise modeling of GaAs HEMTs under illumination. (13th February 2015) - Colangeli, Sergio; Ciccognani, Walter; Limiti, Ernesto; Caddemi, Alina; Crupi, Giovanni; Salvo, Giuseppe; Caddemi, Alina; Caddemi, Ernesto
Abstract The present work is focused on the modeling of the noise performance of GaAs HEMTs under laser illumination. The model is straightforwardly extracted by using a polynomial approximation of the noise correlation parameters without the need for determining an equivalent circuit representation. The validity of the model is confirmed by the observed good agreement between model simulations and noise measurements with and without light up to 26 GHz. Copyright © 2015 John Wiley & Sons, Ltd.